Is the HIV sentinel surveillance system adequate in China? Findings from an evaluation of the national HIV sentinel surveillance system - Marc Bulterys; Keith Sabin; Jesus García Calleja; Zhongdan Chen; Nicole Seguy; Sanny Chen; Wen Lin (Western Pacific Surveillance and Response, 2012)
Background: An external evaluation was conducted to assess the performance of the national HIV sentinel surveillance system (HSS), identify operational challenges at national and local levels and provide recommendations for improvement.Methods: The United States Centers for Disease Control and Prevention’s (CDC) Updated Guidelines for Evaluating Public Health Surveillance Systems were followed to assess the key attributes of HSS. Comprehensive assessment activities were conducted, including: using a detailed checklist to review surveillance guidelines, protocols and relevant documents; conducting self-administered, anonymous surveys with 286 local China CDC staff; and carrying out field observations in 32 sentinel sites in four provinces.Results: China has built an extensive HSS with 1888 sentinel sites to monitor HIV epidemic trends by population groups over time. The strengths of HSS lie in its flexibility, simplicity, usefulness and increase in coverage in locations and populations. With its rapid expansion in 2010, HSS faces challenges in maintaining acceptability, timeliness, data quality, representativeness and sustainability.Recommendations: Implementation of the national guidelines should be standardized by strengthening training, monitoring and supervision of all staff involved, including community-based organizations. National surveillance guidelines need to be revised to strengthen data quality and representativeness, particularly to include specific instructions on HIV testing result provision, collection of identifying information, sample size and sampling methods particularly for men who have sex with men (MSM), collection of refusal information, and data interpretation. Sustainability of China’s HSS could be strengthened by applying locally tailored surveillance strategies, strengthening coordination and cooperation among government agencies and ensuring financial and human resources.